Journal of Midwifery and Women's Health Vol.59, No.5, September-October 2014 - Wiley Subscription Services (Wiley Periodicals, 2014)
-The Lancet Series on Midwifery : A Momentous Opportunity to Improve Maternal and Newborn Health -The Crown Initiative: Journal Editors Invite Researchers to Develop Core Outcomes in Women's Health - Creating a Conversation About Immunizations - Risk Knowledge and Psychological Distress During Pregnancy Among Primiparous Women of Advanced Age and Their Partners - A Socioecological Predication Model of Posttraumatic Stress Disorder in Low-Income, HIgh-Risk Prenatal Native Hawaiian/Pasific Islander Women - Effects of Progressive Muscle RElaxation Exercises Accompanied by Music on Low Back Pain and Quality of Life During Pregnancy - Finding Meaning in Life Following Emergency Postpartum Hysterectomy: What Doesn't Kill Us Makes Us Stronger - Men in MIdwifery: A National Survey - Pilot Test of a Preconception and Midwifery Care Promotion Program for College Women - Comparison of Abstinence and Coital Frequensy Between 2 Natural Methods of Family Planning